Association between diabetes status and breast cancer in US adults: findings from the US National Health and Nutrition Examination Survey - Sun, Xingyu; Zhang, Qiangsong; Kadier, Kaisaierjiang; Hu, Pengcheng; Liu, Xiaozhu; Liu, Jialing; Yan, Yulu; Sun, Chenyu; Yau, Vicky; Lowe, Scott; Meng, Muzi; Liu, Ziru; et al. (Frontiers in Endocrinology, 2023)
Objectives: The purpose of this study was to determine whether breast cancer and diabetes status are related in adult Americans. Methods: We conducted a cross-sectional study of 7,599 individuals from the National Health and Nutrition Examination Survey (NHANES). Diabetes was classified as type 2 diabetes and pre-diabetes. Both prediabetes and diabetes were diagnosed according to ADA 2014 guidelines. Multiple logistic regression analysis was used to explore the relationship between diabetes status and breast cancer. Results: Using two segmented linear regression models to fit the relationship between BMI and breast cancer, an inflection point at 21 was obtained, indicating that BMI affected breast cancer at an inflection point 21 Kg/m2. Using the two-piecewise linear regression model, it was observed that there is a threshold effect in the risk of breast cancer occurrence at the age of 52 years. Specifically, the risk of breast cancer is relatively low before the age of 52 but increases significantly after this age. For Non-Hispanic White individuals, the ORs for BMI and age were 0.99 (95% CI, 0.96-1.03, P=0.7253) and 1.08 (95% CI, 1.05-1.10, P<0.0001), respectively. Similarly, for Non-Hispanic Black individuals, the ORs were 1.01 (95% CI, 0.97-1.05, P=0.6611) for BMI and 1.08 (95% CI, 1.04-1.12, P=0.0001) for age. Conclusions: Diabetes status is associated with the risk of breast cancer development. Moreover, the risk of developing breast cancer steadily increased from non-diabetes to prediabetes and type 2 diabetes. In addition, the prevalence of breast cancer showed a gradual increase with increasing BMI up to 21 Kg/m2 with the highest prevalence of breast cancer. There was an inverse U-shaped relationship between BMI and breast cancer prevalence. Furthermore, age has a threshold effect on the risk of breast cancer in females, with the risk increasing significantly after age 52 years. Finally, it is important to note that the association between BMI/age and breast cancer risk varies across different racial/ethnic groups.